Speech perception in noise in patients with idiopathic sudden hearing loss. (1st April 2022) - Kitoh, Ryosuke; Nishio, Shin-ya; Usami, Shin-ichi
Abstract: Background: Patients with unilateral hearing loss have difficulties perceiving speech in a noisy environment. Unilateral severe to profound hearing loss is most commonly caused by idiopathic sudden sensorineural hearing loss (SSNHL). Objectives: To assess speech perception in noise among patients with idiopathic unilateral SSNHL, and examine the factors affecting the results. Material and methods: We retrospectively enrolled 93 patients with idiopathic unilateral SSNHL. The speech signal was presented at a constant sound pressure level, while the noise signal varied from +5 dB to −5 dB signal-to-noise ratio (SNR) in units of 5 dB (S0/Nhe). Results: As the SNR decreased, the percentage of correct answers also decreased. The correct answer rate decreased with increased hearing level at post-treatment. There was a correlation between age and speech perception, especially when dividing the patients into two groups: <65 years old and ≥65 years old. Conclusions and significance: The results showed that speech perception clearly decreased in a noisy environment rather than in a quiet environment, and the correct answer rate of the speech perception test in noise was significantly correlated with hearing level at post-treatment. This study provides important data for future interventions for unilateral hearing loss, including cochlear implants.